Manufacture of laminated strips board from ivory Bamboo (bambusa vulgaris var. striata) / Muhammad Hanif Mazlan - Mazlan, Muhammad Hanif (Faculty of Applied Sciences, 2017)
The world market for bamboo is lucrative considering billions of USD worth of commodity and bamboo-related products are being traded annually. The increased global awareness and demand for bamboo as one of emerging green products from sustainable resources has led to more usage of bamboo in commercial applications. Realising the potential and importance of bamboo, Malaysia has embarked on concerted efforts to elevate bamboo to become a vital resource commodity. This study was conducted to determine the basic, mechanical and physical properties of ivory bamboo (Bambusa vulgaris var. striata) at different strip orientation and strip layer. The mechanical properties of B. vulgaris var. striata were loaded in bending and internal bonding while the physical properties were density, thickness, swelling and water absorption. The bamboo specimens were selected from bottom part and towards 8 metre up. The specimens were oven dried until 8% moisture content for board manufacture. The board were conditioned to achieve 12% moisture content before tested. The boards were replicated by 4 for each parameter. The statistical analysis showed that there were significantly different for number of board layers and board orientations except for water absorption and thickness swelling at different layers. The board properties indicated that the 3 layers board is stronger than 5 layers board. Meanwhile, the parallel orientation board gave better performance as compared to cross orientation. Therefore, it can concluded that the manufacture laminated strip board was successfully because it has achieve minimum requirement Malaysian Standard (MS 1787) for wood based panel and it has comparable modulus of rupture for flooring accordance to Malaysian Standard (MS 3.44: 1978).